EFL Students’ Translation Strategy of Narrative Text of English Language Education Study Program - Lina Anisah; La Ode Muhammad Idrus Hamid Basri (ELT Worldwide: Journal of English Language Teaching, 2023)
This research aimed to investigate the translation strategies employed by 5th semester students of the English Language Study Program at Sembilanbelas November Kolaka University when translating narrative texts. The authors sought to understand the students' approaches to translating these texts, as well as identify the errors they made throughout the process. By doing so, the authors hoped to provide valuable insights to students regarding the most effective translation strategies and assist them in recognizing and correcting their translation errors. A qualitative research design was utilized to examine the translation strategies of narrative texts. Data collection involved a translation test taken by 30 students, which served as the foundation for the authors' analysis. Based on the findings, the authors concluded that the students mainly implemented three translation strategies to translate narrative texts. The first strategy was literal translation which was used 84% of the time. Literal translation strategy means that the translators translate texts as is. The second strategy that was linguistic amplification. It was used 2.41% of the time. Linguistic amplification is a translation strategy where translators add more details into the TL. The third strategy that was used was generalization at 2.29%. Using this strategy means that the translators decide to use the general term of a word instead of translating it specifically based on the SL. The authors also found out that the most common errors that the students made while translating the texts they were given was incorrect word errors. In other words, the students incorrectly translated the words from the SL to the TL which may cause confusion for the readers. By doing this research it is expected become an insight about language teaching especially on the translation related to translation strategi that used to translate. The appropriate implementation of translation method in translating process will produce accurate translation. The findings of this study underscore the importance of providing targeted instruction on translation strategies for EFL students. By doing so, educators can help students develop the skills and knowledge necessary to produce high-quality translations that effectively convey the meaning and nuances of the source text.